DEVELOPING PROFESSIONAL ENGLISH COMMUNICATION SKILLS FOR TOURISM STUDENTS IN THE POST-COVID TRAVEL INDUSTRY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The global tourism industry has faced a dramatic transformation due to the COVID-19 pandemic, with long-lasting effects on travel behavior, safety protocols, and service expectations. In this new landscape, professional English communication has become even more essential, not only for effective customer service but also for crisis response, health communication, and digital interaction. This paper explores the current needs of the tourism industry in the post-COVID era and identifies key English language competencies required for tourism students. Using a qualitative review of curriculum materials, industry demands, and international reports, the study reveals specific gaps in tourism education and suggests pedagogical strategies for integrating real-world, communicative, and context-sensitive English skills. The paper argues for a shift from traditional transactional English teaching to a more comprehensive, responsive approach tailored to the post-pandemic travel environment.